TEKNIK KOLEKSI DAN PRESERVASI TUMBUHAN JATI (Tectona grandis) DI KELURAHAN TURIDA, KECAMATAN SANDUBAYA, KOTA MATARAM - Karisma Cahyani; Ratna Ariyanti; Karmila Fajriah; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Plant collection and preservation are essential steps in botanical studies to support species identification and biodiversity documentation. This study aims to describe the techniques of collecting and preserving teak (Tectona grandis) in Turida Village, Sandubaya District, Mataram City. The method used was a field survey with direct sampling of representative vegetative parts. Preservation was carried out using herbarium techniques, including pressing, drying, and labeling the specimens. The results indicate that proper collection techniques greatly influence specimen quality, particularly in maintaining key morphological characteristics for accurate identification. In addition, appropriate preservation methods enhance specimen durability for long-term use. Therefore, the application of systematic collection and preservation techniques contributes to botanical research and supports sustainable biodiversity conservation efforts.